Earnings Management and Managerial Honesty: The Investors' Perspectives - Rajna Gibson; Matthias Sohn; Carmen Tanner; Alexander F. Wagner (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2021)
Extant research shows that CEO characteristics affect earnings management. This paper studies how investors infer a specific characteristic of CEOs, namely moral commitment to honesty, from earnings management and how this perception - in conjunction with their own social and moral preferences - shapes their investment choices. We conduct two laboratory experiments simulating investment choices. Our results show that participants perceive a CEO to be more committed to honesty when they infer that the CEO engaged less in earnings management. For investment decisions, a one standard deviation increase in a CEO's perceived commitment to honesty compared to another CEO reduces the relevance of differences in the CEOs' claimed future returns by 40%. This effect is most prominent among investors with a proself value orientation. To prosocial investors, their own honesty values and those attributed to the CEO matter directly, while returns play a secondary role. Overall, perceived CEO honesty matters to different investors for distinct reasons.
urn:nbn:de:hebis:30:3-616471
Keywords: M41; G41; G11; 330; Earnings management; honesty; investor preferences; investor segmentation; protected values